Quantificação imunofenotípica de células T reguladoras em cães acometidos por linfoma multicêntrico submetidos ao protocolo quimioterápico chop associado ou não a um firocoxib - Anai, Letícia Abrahão [UNESP] (2014)
In Veterinary Medicine lymphoma is a neoplasm characterized by clonal proliferation of malignant lymphocytes, one of the most common in dogs. There is evidence that Treg inhibit the effector function against tumors, resulting in T cell dysfunction in humans and dogs with cancer. Increased expression of cyclooxygenase-2 enzyme (COX-2) by tumor cells and local inflammatory cells, stimulates the development of Treg. Thus, treatment with COX-2 inhibitors such as nonsteroidal anti-inflammatory is a further strategy for the removal of Tregs. In this context, this work aimed to evaluate quantitatively, through flow cytometry, Tregs in dogs with lymphoma undergoing chemotherapy protocol CHOP, with or without a COX-2 inhibitor (Firocoxib). 12 dogs were used controls (healthy), 12 dogs with lymphoma treated with CHOP protocol and 12 dogs with lymphoma treated with CHOP + Firocoxib. Tregs form assessed by flow cytometry at diagnosis after induction chemotherapy (Week 5) and the protocol termination (20 weeks). The results showed that dogs with lymphoma had higher percentages of Tregs (17.08 ± 1.62) compared with the control group (5.67 ± 1.62) (p <0.0001). Moreover, in the lymphoma group had a decrease of Treg percentages at the end of chemotherapy protocol, the groups treated with the traditional CHOP protocol (GT1) (8.648 ± 1.736) and in the CHOP arm associated with a firocoxib (GT2) (5,903 ± 1.126) (p <0.0001). And that between the groups, GT1 (20.66 ± 2.487), and GT2 (12.79 ± 0.7673) only at the time of diagnosis (M0), was statistically different (p <0.0114). It was concluded that dogs with multicentric lymphoma has increased Tregs, and during the chemotherapy protocol, with or without a firocoxib, these cells decrease significantly